Angina de peito. Isquemia silenciosa. - J L Tuna (Acta Médica Portuguesa, 1997)
One of the most difficult problems related to coronary artery disease is the detection and eventual treatment of silent myocardial ischemia (SMI). After defining the concept of SMI and total ischemia burden, the author approaches the pathophysiology of myocardial ischemia and focuses on the ischemic cascade. Concerning the detection of SMI the importance of exercise testing and Holter ECG is stressed. Following the classification of SMI proposed by P. F. Cohn, the author analyzes SMI type III with particular interest. He refers the prevalence of SMI in patients suffering from chronic stable angina, and focuses on the prognostic importance of SMI. Afterwards, the problem of treatment and prognostic implications is approached. The paper ends with mention of the results of the most important clinical trials in this field: CASIS, CAPE, TIBBS, ASIST, ACIP, TIBET.